2010
DOI: 10.1016/j.immuni.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Germinal Center Responses Require a Multistage T Cell:B Cell Adhesion Process Involving Integrins, SLAM-Associated Protein, and CD84

Abstract: CD4+ T cells deficient in signaling lymphocyte activation molecule (SLAM)-associated protein (SAP) exhibit a selective impairment in adhesion to antigen presenting B cells but not dendritic cells (DC), resulting in defective germinal center formation. However, the nature of this selective adhesion defect remained unclear. We found that whereas T:DC interactions were primarily integrin-dependent, T:B cell interactions had both an early integrin-dependent phase and a sustained phase that also required SAP. We fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
428
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(463 citation statements)
references
References 41 publications
23
428
3
Order By: Relevance
“…6B). In this experimental system, any effects of TLR signaling in B cells on T FH cell function would likely be reflected equally by both types of B cells, because it is known that cognate interactions between T FH cells and GC B cells are short-lived relative to the time frame of the GC responses being analyzed (63)(64)(65)(66). Thus, B cell-intrinsic TLR9 signaling improved selection of antigen-specific B cells into the GC compartment, boosted their expansion, and/or enhanced their survival.…”
Section: Discussionmentioning
confidence: 99%
“…6B). In this experimental system, any effects of TLR signaling in B cells on T FH cell function would likely be reflected equally by both types of B cells, because it is known that cognate interactions between T FH cells and GC B cells are short-lived relative to the time frame of the GC responses being analyzed (63)(64)(65)(66). Thus, B cell-intrinsic TLR9 signaling improved selection of antigen-specific B cells into the GC compartment, boosted their expansion, and/or enhanced their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, SLAM receptors are capable of regulating either homotypic-or heterotypic-cell/cell interactions between immune cells. Through investigations of XLP patients and genetargeted mice, a common theme has emerged for SAP in regulating lymphocyte-lymphocyte contact, communicating signals necessary for lymphocyte differentiation and executing effector function: CD4 C T cell-B cell interactions in generating T FH cells, germinal centers, B cell isotype-switching and B cell memory; [14][15][16][17] thymocyte-thymocyte interactions instructing the development of NKT cells; [18][19][20] NK cell-haematopoietic target interactions controlling cytotoxicity [21][22][23] and effector CD8 T cell-B cell interactions modulating CD8…”
Section: Introductionmentioning
confidence: 99%
“…Earlier evidence in vitro suggested that CD84 and Ly108, both highly expressed by activated T and B cells, positively promote Ag-specific T-B adhesion in an SAP-dependent fashion (9). A more recent study indicates that, in the absence of SAP, Ly108 transmits inhibitory signals into the T cells to dampen their adhesive interactions with B cells (37).…”
mentioning
confidence: 99%